Design and Development of An Integrated Monitoring System for Nebulizer and Infusion for Lung Disease Patients Based on IoT - Atha Azhar Arrafi; Farida Arinie Soelistianto; Moh. Abdullah Anshori (West Science Interdisciplinary Studies, 2024)
This research develops an Internet of Things (IoT)-based monitoring system for nebulizers and infusion devices for patients with lung diseases, specifically Acute Respiratory Infections (ARI). The aim is to improve nursing efficiency and minimize the risk of complications due to delayed patient care by enabling remote monitoring and providing real-time information on the status of nebulizers and infusion devices via a website. The system is designed to stop the infusion fLow when the required amount is reached and to automatically turn off the nebulizer when there is no liquid. It uses an ESP32 microcontroller to control IR obstacle sensors, relays, and a servo motor for the infusion clamp, as well as an LCD display for digital information and feature displays. The system is also equipped with an alarm to indicate when the infusion liquid or nebulizer is depleted and a website to provide real-time status information to medical personnel. Testing shows that the system has a high accuracy of 98.7% and minimal error of approximately 1.82% in monitoring and controlling nebulizer and infusion fluids. In conclusion, the system successfully improves nursing efficiency and patient safety while reducing the workload of nurses through the automation of medical devices that were previously managed manually.